Pemanfaatan Metode SAS (struktural analitik sintetik) Dalam Meningkatkan Kemampuan Membaca Permulaan Dan Menulis Permulaan Siswa Tunarungu Wicara - Maria Agustina Mera; Rudy Sumiharsono; Kustiyowati Kustiyowati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
The purpose of this study is to describe the use of the SAS (Synthetic Structural Analytical) method in improving the beginning reading and writing skills of first graders with speech impairments. This research is a class action research (CAR). Data collection techniques are carried out through observation, documentation, and tests. Data analysis was carried out in this study using descriptive analysis, namely data reduction, data presentation, and drawing conclusions. The results of the study show that: 1) using the synthetic structural analytic method (SAS) can improve the beginning reading and writing skills of grade 1 students, 2) using the synthetic structural analytic method (SAS) in learning to read beginning and start writing is carried out in stages, namely two cycles experienced a significant increase where students in cycle 1 were categorized as 'less' than the average value of 66.6 and in cycle II they increased to the category of 'very good' with an average value of 81.1. Thus the synthetic structural analytic method (SAS) needs to be used as a reference by teachers in early reading and writing learning activities in elementary schools.